Neuroimaging of neuronal circuits involved in tic generation in patients with Tourette syndrome - Lerner, A; Bagic, A; Boudreau, E A; Hanakawa, T; Pagan, F; Mari, Z; Bara-Jimenez, W; Aksu, M; Garraux, G; Simmons, J M; Sato, S; Murphy, D L; et al. (Neurology, 2007)
To identify brain regions generating tics in patients with Tourette syndrome using sleep as a baseline. We used [15O]H2O PET to study nine patients with Tourette syndrome and nine matched control subjects. For patients, conditions included tic release states and sleep stage 2; and for control subjects, rest states and sleep stage 2. Our study showed robust activation of cerebellum, insula, thalamus, and putamen during tic release. The network of structures involved in tics includes the activated regions and motor cortex. The prominent involvement of cerebellum and insula suggest their involvement in tic initiation and execution.